IDENTIFIKASI KARAKTER MORFOLOGI DAN AGRONOMI BEBERAPA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DI DATARAN TINGGI - Cucu Utari Alfiani; Bastaman Syah; Elia Azizah; Prasodjo Soedomo (Jurnal Ilmiah Wahana Pendidikan, 2021)
The different varieties used are the same growing environment will provide an overview of the application of varieties. The different varieties used are aimed at seeing the right variety for planting in the highlands as well as a better appearance. The research was carried out in the home screen of the experimental garden of the Vegetable Research Institute located in Cikole Village, Lembang District, West Bandung Regency. From September to December 2020. The research method used was a single factor randomized block design (RBD) with 9 replications. Treatment 3 was A (Bima Brebes variety), B (Pancasona variety), and C (Violetta-2 variety) so there were 27 experimental units. Treatment analysis with analysis test and analysis test 5% is significant, so to see the best treatment with the Least Significant Different (LSD) test at the 5% level. The results showed that there was a significant effect of varieties on plant height, number of leaves, number of tillers, tuber length, tuber diameter, wet tuber weight per plant, wet tuber weight per plot and dry tuber weight per plot. Treatment C (Violetta-2 variety) gave the highest yield in plants (49.81 cm), number of leaves (16.76), tuber length (26.60 mm), tuber diameter (20.69 mm), wet tuber weight. per plant (20.72 grams), wet tuber weight per plot (60.14 grams), and dry tuber weight per plot (49.81 grams). Meanwhile, treatment B (Pancasona variety) gave the highest yield in the number of tillers (4.59 tillers). Keywords : Agronomy, Highlands, Morphology, Shallots, Varieties